Enseñanza de las matemáticas - PIAGET, Jean (AGUILAR, 1965)
Otros autores: BETH, Edward W.; DIEUDONNE, Jean; GATTEGNO, Caleb; CHOQUET, Gustave; LICHNEROWICZ, Andre. Otros descriptores: GEOMETRIA NO EUCLIDEANA.